1998
DOI: 10.1021/jp981135i
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bystander Substituents on the Rates of 1,2-H and 1,2-Ph Shifts in Singlet and Triplet Carbenes

Abstract: Substituent effects at the migration origin on the rate of rearrangement of several alkylchlorocarbenes have been studied at the B3LYP/6-311G**//B3LYP/6-31G* level. Methyl, halo, and phenyl groups are found to accelerate 1,2-H shift rearrangements in the order Ph > Me > F > Cl > H. Methyl groups are also found to accelerate both singlet and triplet 1,2-Ph shifts in benzylchloro- and benzylcarbenes. A direct comparison of the 1,2-H shift in methylchlorocarbene and the 1,2-Ph shift in benzylchlorocarbene shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…From the ear lier com pu ta tional stud ies, the pre dicted Ea's of CH2Y-C-Cl seem to be larger than those of the cor re spond ing CH 2 Y-C-CH 3 spe cies. 16,17 In our early anal y sis, we found that the dif fer ences in E a for these two sets of carbenes (X=Cl and Me) are rel a tively large. The view point of by stander ef fect may not be the ma jor fac tor ac count ing for the re ac tiv ity of carbenes to ward 1,2-H shift.…”
Section: Scheme Imentioning
confidence: 93%
See 3 more Smart Citations
“…From the ear lier com pu ta tional stud ies, the pre dicted Ea's of CH2Y-C-Cl seem to be larger than those of the cor re spond ing CH 2 Y-C-CH 3 spe cies. 16,17 In our early anal y sis, we found that the dif fer ences in E a for these two sets of carbenes (X=Cl and Me) are rel a tively large. The view point of by stander ef fect may not be the ma jor fac tor ac count ing for the re ac tiv ity of carbenes to ward 1,2-H shift.…”
Section: Scheme Imentioning
confidence: 93%
“…21 Stereochemistry of carbenes has been stressed in pre vious com pu ta tional stud ies. 16,22 In this re search, PESs of both cis and trans con form ers were stud ied. The ex cep tions are CH 3 -C-X and CH 2 Y-C-H, be cause only cis con form ers ex ist in these carbenes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to the most frequently found migratory aptitudes of H>Ph>Me 3. However, it has been shown that the tendency of the rearrangement is strongly influenced not only by the nature of the migrating group X, but also by the bystander substituents R 1 and R 2 at the migration origin and by the spectator substituent R 3 2b. 4 Furthermore, 1,2‐rearrangement reactions of carbenes may be affected by the type of carbene precursor that is used and the reaction conditions, such as solvent polarity and temperature.…”
Section: Introductionmentioning
confidence: 99%